Numerical Analysis of Progressive Collapse of Steel Frame Building - Ali, Mohammed A.; Falah, Nabil (University of Science and Technology, Yemen, 2014)
In this study, the progressive collapse resistance of a two-story steel gravity frame was investigated numerically after the sudden removal of a perimeter column in the first floor. A comparison of the numerical analyses results and experimental results was available in the literature [1]. After the model validation, the effect of infill steel panels and bracing on enhancing the progressive collapse resisting capacity of gravity frame were evaluated. The progressive collapse models were simulated by arbitrarily removing a perimeter column and carrying out nonlinear static analyses using the finite element analysis code ABAQUS.